Monolingual cringe and ideologies of English: Anglophone migrants to Luxembourg draw their experiences in a multilingual society - de Bres J; Lovrits V (Taylor and Francis Group, 2021)
This article uses reflective drawing to explore representations of multilingualism by Anglophone migrants in Luxembourg. Analysing twelve interviews in which participants drew and described their language experiences, we examine the language ideologies Anglophone migrants adopt in response to the ideologies of English they encounter. Participants adopt various ideologies, sometimes aligning with the ideology of global English, sometimes with counter-ideologies of resistance to it, and sometimes a mix of the two. Visual features indexing affective states include colour, gesture, facial expression, and composition. Monolingual cringe – expressed as shame, embarrassment and being ‘bad at languages’ – performs several functions for the participants. Sometimes it serves as an affective disclaimer, allowing them to lean on their privilege in a more socially acceptable way. Sometimes it appears to express genuine distress, in the form of searing linguistic insecurity. Sometimes it performs a distancing function, enabling them to oppose themselves to the stereotype of the monolingual English speaker. The affective intensity of the drawings suggests the ideology of global English does have costs for Anglophone migrants. Fundamentally, though, monolingual cringe reinforces privilege, allowing participants to apologise for their monolingualism even as they continue to benefit from it.
Keywords: Language ideologies; English; multilingualism; drawing